Implikasi Hukum Pajak PPH Dan PPN Terhadap Investasi Aset Kripto Di Indonesia - Amalia, Rizki Fitri; Kancana, Haqkida; Jabarti, Ahmad; Kesuma, Joni (Consensus : Jurnal Ilmu Hukum, 2026)
The increase in transactions and the number of crypto asset investors has legal implications, particularly in taxation, which requires adaptive, fair, and legally certain tax policies. This study aims to analyse the impact of Income Tax (PPh) and Value Added Tax (PPN) on crypto asset investment in Indonesia, in order to provide legal certainty and protection for investors, as well as to support state revenue. This study uses a normative legal method with a legislative, conceptual, and case approach. Legal materials were obtained through a literature study that was analysed qualitatively and prescriptively. The results of the study show that the imposition of PPh and PPN on crypto assets has provided a basis for legal certainty by establishing crypto assets as valid taxable objects, as well as encouraging administration and taxpayer compliance. However, the volatility and cross-border nature of crypto assets pose challenges for tax fairness and collection effectiveness, related to rapid regulatory changes, jurisdictional limitations, and low investor tax literacy. This study concludes that there is a need to strengthen a more stable legal framework for crypto taxation, harmonise regulations across sectors, and improve tax education to create fair, certain, and sustainable tax policies in Indonesia's digital investment ecosystem.